Investigation of the influence of technological extrasion methods of pulp on the composition and quantitative content of phenolic substances in red natural wine materials - H. R. Siyukhov; T. A. Ustyuzhaninova; O. M. Rodina (Новые технологии, 2019)
The article presents the results, studies of the influence of various methods of extracting pulp on changes in qualitative composition and quantitative content of phenolic substances in red dry wine materials of the Saperavi variety.Extraction of the pulp was carried out by complete and partial fermentation of the wort on the pulp with preliminary fermentation, with pulp heating and carbon dioxide maceration.It’s been found that the method of pulp extraction has a significant effect on the mass concentration of flavonoids (anthocyanins, catechins and flavonols);The extraction method has a significant impact on the qualitative composition and quantitative content of monomeric forms of phenolic substances - phenol carboxylic acids of benzoic and cinnamon series (C6 - C1 and C6 - C3).For the Saperavi variety, the largest number of phenolic acids has been identified in the wine material obtained by carbon dioxide maceration;A significant difference has been found in mass concentrations of phenolic acids in wine materials obtained by different methods for pulp extraction. The smallest number of phenolic acids has been found at extracting pulp by heating;Processing the pulp with an enzyme preparation increases the content of phenolic compounds in the wine material, including anthocyanins, which determine the completeness of the taste, aroma and color of the wine.